Seasonal spreading and age of Citarum River water in the Jakarta Bay. Issue 1 (1st January 2023) - Soeyanto, E; Morimoto, A; Hayami, Y; Sudaryanto, A
Abstract: Citarum River is considered one of the most polluted rivers in the world, which could contribute to Jakarta Bay's environmental quality. The purpose of this study is to predict the impact of the Citarum River on Jakarta Bay's pollution by understanding the river's seasonal spreading and water age. This study uses numerical ocean modeling for the largest river flowing to Jakarta Bay in 2016. The constituent-oriented age and residence time theory (CART), which supports a solution to the environmental problems in this bay, was employed to comprehend long-term river water movement. The CART's water age calculation module is embedded in a numerical hydrodynamic model to generate the temporal variation and spatial distribution of Citarum River water. Hydrographic observations were used to validate the model in February, May, and November this year. Surface current distribution patterns, which were controlled by surface wind stress and river discharge, determined the seasonal spread of the Citarum River water distribution. Meanwhile, the average age of Citarum River water in Jakarta Bay was a few days.